The Influence of Motivation, Discipline and Work Enviroment on Employee Performance in the Directorate of Planning, Organization and General Affairs our Hope Heart and Blood Vessel Hospital - Rahayu, Yuni Mardi; Pujiati, Herni (Dinasti International Journal of Digital Business Management, 2025)
Globalization in the world of the health industry continues to develop every time and every year, this causes competition in the business world, especially in the health service sector to increase. Then, with the implementation of the MEA (Asean Economic Community) agreement, the impact of which will lead to competition in the economy in the ASEAN region, the quality of business products and human resources will be more required to be competent. On this basis, the authors conducted a study entitled "The Influence of Motivation, Discipline and Work Environment on Employee Performance at the Directorate of Planning, Organization and General Affairs at Harapan Kita Heart and Blood Vessel Hospital. The results showed that there was a significant influence between Motivation, Discipline and Work Environment with Employee Performance This can be seen based on the t-test on the work motivation variable showing that there is a significant effect on employee performance with a t-count value (4.756) > t table. (1.641) and a significant value of 0.000 <0.05. The results of the t-test on the Work Discipline variable show that there is a significant effect on employee performance with a t-count value (0.689) < t table (1.641) and a significant value of 0.495> 0.05. The results of the t-test on the work environment variable showed that there was an effect but not significant on employee performance with a t-count value (1.412) < t table (1.641) and a significant value of 0.166> 0.05. The results of the analysis output from the calculated F value of 34.852> 2.750 with a significant value of 0.000 <0.05 so it can be concluded that Work Motivation, Discipline and Work Environment have a significant positive influence simultaneously on Employee Performance.